2009
DOI: 10.1016/j.nurt.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Developing Novel Antiepileptic Drugs: Characterization of NAX 5055, a Systemically-Active Galanin Analog, in Epilepsy Models

Abstract: The endogenous neuropeptide galanin and its associated receptors GalR1 and GalR2 are highly localized in the brain limbic structures and play an important role in the control of seizures in animal epilepsy models. As such, galanin receptors provide an attractive target for the development of novel anticonvulsant drugs. Our efforts to engineer galanin analogs that can penetrate the blood-brain-barrier and suppress seizures, yielded NAX 5055 (Gal-B2), a systemically-active analog that maintains low nanomolar aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 39 publications
3
82
0
Order By: Relevance
“…Cationization and lipidization of galanin (1-13) provided two galanin analogues, Gal-B2 and [B-Me, des-Sar]Gal-B2, which are metabolically stable and CNS-penetrating. Both analogues are highly active in 6-Hz model of pharmacoresistant seizures upon systemic administration (30)(31)(32)(33). In addition, Gal-B2 is active in the Frings audiogenic seizure-susceptible mouse and in the corneal kindling model of partial epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cationization and lipidization of galanin (1-13) provided two galanin analogues, Gal-B2 and [B-Me, des-Sar]Gal-B2, which are metabolically stable and CNS-penetrating. Both analogues are highly active in 6-Hz model of pharmacoresistant seizures upon systemic administration (30)(31)(32)(33). In addition, Gal-B2 is active in the Frings audiogenic seizure-susceptible mouse and in the corneal kindling model of partial epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been made in recent years toward development of systemically active agonists/ modulators for GalR1 and GalR2 receptors and, as of today, two nonpeptide, systemically active agonists, Galnon (17) and Galmic (29), and a CNSpenetrating peptide, galanin analogue Gal-B2 (30)(31)(32)(33), have been synthesized and characterized. All three galanin receptor agonists have been shown to exhibit potent anticonvulsant effect upon systemic application.…”
mentioning
confidence: 99%
“…We have previously shown enhanced metabolic stability, blood-brain-barrier penetration, and antiseizure activity of modified galanin analogs that contain a critical amount of lipophilicity and cationization to rationally selected domains of the active galanin neuropeptide (Bulaj et al, 2008). Our prototype galanin analog, NAX 505-5, has demonstrated potent antiseizure activity in several animal models (White et al, 2009;Jequier Gygax et al, 2014). We have also recently shown that peptides containing monodisperse oligoethyleneglycol (dPEG) modifications, with minimal penetration into the central nervous system, effectively reduce pain-related behaviors in the formalin and carrageenan models of pain (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…To design such NPW-derived compounds, we employed the lipidizationcationization strategy that was successfully applied toward systemically active analogues of GAL, NT, and NPY (GAL-B2, NT-BBB1, and NPY-BBB2, respectively)- (10,(20)(21)(22)(23). Structures and summary of anticonvulsant and physicochemical properties of GAL-B2, NT-BBB1 and NPY-BBB2 are provided in Figure S2 in the Supporting Information.…”
mentioning
confidence: 99%
“…Design of BBB-permeable NPW analogues was based on previous structure-activity relationship (SAR) findings that the C-terminal fragment NPW [14][15][16][17][18][19][20][21][22][23] and the N-terminal tripeptide of NPW are important for its structural and functional properties (24). Furthermore, Kanesaka and co-workers constructed centrally truncated analogues of NPW in which nonessential amino acid residues were replaced by backbone spacer units (5-aminovaleric acid), resulting in potent and selective NPWB 1 agonists (12).…”
mentioning
confidence: 99%